Cytotoxic Effect of Two Novel Platinum (II) Complexes on Breast Cancer: An in Vitro Study - Akbarzadeh, Samad; Ebrahimi, Fatemeh; Faghih, Zeinab; Movahed, Ali; Faghih, Zahra (Asian Pacific Journal of Cancer Biology, 2018)
Background: With 1.36 million new cases in worldwide each year, breast cancer (BC) is the most common malignancy in the female. Among numerous chemotherapy drugs which are widely used for cancer therapy, platinum compounds are the most persuasive ones although challenges remain with the clinical use of them due to their side effects as well as intrinsic and acquired resistance. In the attempt to combat drug resistance, reduce cytotoxic side effects or find the drug for particular forms of cancer, over the years, thousands of other platinum (Pt) compounds i.e. carboplatin and oxaliplatin have been developed. Material and Methods: In this regard, we previously described the synthesis of some new platinum (II) derivatives with potential anti-cancer activities against BC. Here, we chose two of the best platinum(II) compounds, 3b and 2a, to further evaluate their cytotoxic activities against human BC cell lines, SKBR3, MCF-7, MDA-MB-231, and MBA-MB-468, with different molecular subtypes using a colorimetric MTT cytotoxic assay. Their cytotoxic activities were compared to cis-platin as a positive control. Results: Our result showed that both compounds had better cytotoxic effect against BC cell lines than cis-platin in particular in the case of triple-negative subtype. Conclusion: These results suggest these compounds as potentially valuable agents for the treatment of breast cancer patients.